LICITAÇÕES DE PROJETOS: O CONCURSO DE ARQUITETURA DA UNIVERSIDADE FEDERAL DO PAMPA - Yamauchi, Vander; Wiese, Ricardo Soccas (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The public tender in Brazil allows the architecture contests as a procedure to contract the architecture or urbanistic projects. Despite this, there is no legal regulamentation of contests, only a normative made by the Brazilian Institute of Architects (IAB), in which is based most of the tenders. This article presents a case study of an architecture contest that occured at the Universidade Federal do Pampa (a federal university of Brazil). The data, obtained from institutional documents, shows that the public institution did not follow totaly the normative of IAB. However, no problems were reported although it requires attention mainly in the preparation of the public notice and the selection of the members of the jury. The architecture constests seem to be a viable procedure for public project contracts.